An evaluation of urbanisation processes in suburban zones using land-cover data and fuzzy set theory - Cieślak Iwona; Górecka Kamila (Bulletin of Geography. Socio-Economic Series, 2021)
The aim of this article was to evaluate urbanisation processes in space using the CORINE Land Cover (CLC) databases. The study was conducted in the rural municipality of Dywity in the direct vicinity of the city of Olsztyn. Basic concepts and methods for evaluating urbanisation processes were determined based on a review of the literature. The article addresses issues related to spatial management and GIS as a data source and a tool for analysing land management activities. The search for new methods for evaluating spatial management and spatial processes plays a particularly important role in rapidly urbanising areas. The study explored the applicability of GIS as a data source and a tool for evaluating urbanisation processes in studies that rely on modern methods such as fuzzy set theory. The intensity and dynamics of urbanisation processes were evaluated based on changes in land cover with the use of CLC databases.